2013
DOI: 10.1186/1556-276x-8-480
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering of suspended monolayer graphene

Abstract: The interactions between phonons and electrons induced by the dopants or the substrate of graphene in spectroscopic investigation reveal a rich source of interesting physics. Raman spectra and surface-enhanced Raman spectra of supported and suspended monolayer graphenes were measured and analyzed systemically with different approaches. The weak Raman signals are greatly enhanced by the ability of surface-enhanced Raman spectroscopy which has attracted considerable interests. The technique is regarded as wonder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This phenomenon agrees with the surface limited diffusion [34,35,36,37]. This process can be attributed to the variation of the surface diffusion coefficient with temperature [40]. Due to the differences in the chemical potentials among the Ag nanoislands, the smaller nanoislands are thermodynamically unstable and they dissolve in atoms for each fixed temperature [41].…”
Section: Resultssupporting
confidence: 66%
“…This phenomenon agrees with the surface limited diffusion [34,35,36,37]. This process can be attributed to the variation of the surface diffusion coefficient with temperature [40]. Due to the differences in the chemical potentials among the Ag nanoislands, the smaller nanoislands are thermodynamically unstable and they dissolve in atoms for each fixed temperature [41].…”
Section: Resultssupporting
confidence: 66%
“…Moreover, with the increase of temperature, small particles are lessened and the value distribution of AgNIs diameter became more concentrated, which indicated that the substrate becomes more uniform. The changes in the AgNIs morphologies at different temperatures are completed via surface-limited diffusion 25 , 26 , which is analogous to ostwald ripening. This process can be attributed to the varying of surface diffusion coefficient with temperature 27 .…”
Section: Resultsmentioning
confidence: 98%
“…Table compares the characteristics of the enhancement technique in this study with those of other techniques reported previously. Although the Raman/PL signals of 2D materials have been enhanced significantly in previous studies when using plasmonic nanostructures and photonic crystal cavities, several external disturbances (e.g., peak shifting, peak distortion) would arise, making characterization with these techniques difficult. In contrast, the thin film-based interference enhancement method appears be a superior method for increasing the light outcoupling of 2D materials because the high enhancement effect occurs without affecting the spectral properties.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, enhancing the Raman and PL signals, in other words, the light outcoupling, of 2D materials has become particularly important for detailed analyses of their fine structural characteristics. Although several techniques have been developed previously to increase the Raman or PL signals of 2D materials, they usually disturb the external properties of the 2D materials in an unpredictable manner, making it difficult to characterize the original Raman or PL spectra. In addition, simple approaches toward enhancing both the Raman and PL emissions of a range of 2D materials have not been reported previously.…”
mentioning
confidence: 99%
See 1 more Smart Citation